ANALISIS KESIAPSIAGAAN UPTD PUSAT PENANGGULANGAN KRISIS KESEHATAN (P2KK) DINAS KESEHATAN ACEH DALAM MENGHADAPI BENCANA GEMPA BUMI - Irhas Farizi; Nizam Ismail; T. Budi Aulia (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
The problem in this research is how the preparedness of UPTD staff of Health Crisis Center (P2KK) of Aceh Health Office in facing earthquake disaster. This study aimed to analyze knowledge and attitude, policies and guidance, emergency response plan, and strategy of resource mobility of UPTD P2KK staff of Dinas Kesehatan Aceh in handling earthquake disaster in Aceh. This research uses descriptive research method with quantitative and qualitative approaches. This research uses primary data and secondary data. Population used in this research is all officer UPTD P2KK Dinas Kesehatan Aceh. Samples were taken as many as 54 people in Sampling Population. Data collection was done by documentation study, interview study, and distribution of questionnaires distributed to all field officers UPTD P2KK Dinas Kesehatan Aceh using the formula of percentage. The results will be analyzed univariat to know the level of preparedness of UPTD P2KK staff of Aceh Health Office in the face of earthquake disaster. Based on the result of the research, it can be concluded that the preparedness of UPTD P2KK Dinas Kesehatan Aceh in coping with the earthquake disaster in Aceh is in ready category. Therefore, staff capacity building is still needed such as training and simulation of earthquake preparedness and sustainability and reinforce each other in 7 sub-clusters of health that are currently active so that UPTD P2KK staff of Aceh Health Office are more competent in facing what happened.